MPLS next steps - Davie, Bruce S. (Morgan Kaufmann series in networking, 2008)
SHORT DESCRIPTION: Multiprotocol Label Switching (MPLS) is a data plane and control technology that is used in packet (that is Internet Protocol) networks. Now over ten years old, it has taken root firmly as a fundamental tool in many service provider networks. The last ten years have seen a considerable consolidation of MPLS techniques and protocols. This has resulted in the abandoning of some of the original features of MPLS, and the development of other new features. MPLS has moved from a prospective solution, to a grown-up technology. Now that MPLS has reached this level of maturity, these new tools and features allow more sophisticated services to the users of the network. These tools and features are discussed within various contexts throughout several networking-related books published by MK and this presents us with a unique publishing opportunity.